Postgraduate admission & promotion survey - Mohd. Nor, Latifah; Wok, Saodah (Research Centre, International Islamic University Malaysia, 2006)
This Postgraduate Admission and Promotion Survey aims to investigate the postgraduate enrolment in the International Islamic University Malaysia in its mission to enhance the postgraduate programme of the institution. Specifically, this research explores the strengths, weaknesses, opportunities and threat of postgraduate programme of this university. Pursuing higher education at the postgraduate level has been a trend among the Malaysian for the past decade. This phenomenon is further enhanced by the government public policy in the effort to move from a production-based economy to a knowledge-based economy. These factors further reinforce postgraduate enrolment in this country that simultineously opens the doors of opportunities to the nation's institution higher learning.